Detection of Influenza in Managed Quarantine in Australia and the Estimated Risk of Importation. (12th August 2022) - Peck, Heidi; Anbumurali, Nithila; McMahon, Kimberley; Freeman, Kevin; Aziz, Ammar; Gillespie, Leah; Yang, Bingyi; Moselen, Jean; Deng, Yi-Mo; Cowling, Benjamin J; Barr, Ian G; Subbarao, Kanta; et al.
Abstract: Background: Influenza circulated at historically low levels during 2020/2021 due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic travel restrictions. In Australia, international arrivals were required to undergo a 14-day hotel quarantine to limit new introduction of SARS-CoV-2. Methods: We usedtesting data for travelers arriving on repatriation flights to Darwin, Australia, from 3 January 2021 to 11 October 2021 to identify importations of influenza virus into Australia. We used this information to estimate the risk of a case exiting quarantine while still infectious. Influenza-positive samples were sequenced, and cases were followed up to identify transmission clusters. Data on the number of cases and total passengers were used to infer the risk of influenza cases exiting quarantine while infectious. Results: Despite very low circulation of influenza globally, 42 cases were identified among 15 026 returned travelers, of which 30 were A(H3N2), 2 were A(H1N1)pdm09, and 10 were B/Victoria. Virus sequencing data identified potential in-flight transmission, as well as independent infections prior to travel. Under the quarantine strategy in place at the time, the probability that these cases could initiate influenza outbreaks in Australia neared 0. However, this probability rose as quarantine requirements relaxed. Conclusions: Detection of influenza virus infections in repatriated travelers provided a source of influenza viruses otherwise unavailable and enabled development of the A(H3N2) vaccine seed viruses included in the 2022 Southern Hemisphere influenza vaccine. Failure to test quarantined returned travelers for influenza represents a missed opportunity for enhanced surveillance to better inform public health preparedness. Abstract : Despite low circulation of influenza, 42 cases were identified among 15 026 travelers in quarantine in Darwin, Australia, in 2020. Testing during quarantine is an important source of viruses for influenza vaccine strain selection and underscores the potential for influenza epidemics as global travel resumes.